Place matters : criminology for the twenty-first century - Weisburd, David (New York, NY : Cambridge University Press, 2016)
Over the last two decades there has been increased interest in the distribution of crime and other antisocial behavior at lower levels of geography. The focus on micro geography and its contribution to the understanding and prevention of crime has been called the 'criminology of place'. It pushes scholars to examine small geographic areas within cities, often as small as addresses or street segments, for their contribution to crime. The authors describe what is known about crime and place, providing an up-to-date and comprehensive survey to date.
Crime places within criminological thought -- The concentration of crime at place -- Theories of crime and place -- The importance of place in mainstream criminology and related fields: influences and lessons to be learned -- Methods of place-based research -- Reducing crime at high crime places: practice and evidence -- Crime places in the criminological imagination.
Includes bibliographical references and index.
Keywords: Criminology; SOCIAL SCIENCE -- Criminology; 71.65 criminality as a social problem